The role of proteasomes in tumorigenesis - Xiangyi Zhou; Ruqing Xu; Yue Wu; Li Zhou; Tingxiu Xiang (Genes and Diseases, 2024)
Protein homeostasis is the basis of normal life activities, and the proteasome family plays an extremely important function in this process. The proteasome 20S is a concentric circle structure with two α rings and two β rings overlapped. The proteasome 20S can perform both ATP-dependent and non-ATP-dependent ubiquitination proteasome degradation by binding to various subunits (such as 19S, 11S, and 200 PA), which is performed by its active subunit β1, β2, and β5. The proteasome can degrade misfolded, excess proteins to maintain homeostasis. At the same time, it can be utilized by tumors to degrade over-proliferate and unwanted proteins to support their growth. Proteasomes can affect the development of tumors from several aspects including tumor signaling pathways such as NF-κB and p53, cell cycle, immune regulation, and drug resistance. Proteasome-encoding genes have been found to be overexpressed in a variety of tumors, providing a potential novel target for cancer therapy. In addition, proteasome inhibitors such as bortezomib, carfilzomib, and ixazomib have been put into clinical application as the first-line treatment of multiple myeloma. More and more studies have shown that it also has different therapeutic effects in other tumors such as hepatocellular carcinoma, non-small cell lung cancer, glioblastoma, and neuroblastoma. However, proteasome inhibitors are not much effective due to their tolerance and singleness in other tumors. Therefore, further studies on their mechanisms of action and drug interactions are needed to investigate their therapeutic potential.